Artistic Activities and Developing Creative Thinking Skills among Children in Early Childhood (American Journal of Human Psychology, 2024)
The study explores the pivotal role of artistic activities in cultivating creative thinking skills during early childhood in identifying the profound impact of these activities on children’s cognitive, emotional and social development. Grounded in Piaget’s cognitive development theory and Gardner’s theory of multiple intelligence has shown the influence of different factors that have included pedagogical approaches, parental involvement, cultural background, and the age and duration of artistic engagement. The literature review has shown the foundational principles of creative thinking programs in early childhood education, emphasising the need for innovative and balanced approaches. Also, with the help of a survey, 300 participants of data were gathered that were teachers and caregivers. Content analysis has been done to get subjective results. The study has included the importance of incorporating artistic activities into educational settings and parents’ support, highlighting the consistent dynamics shaping creativity outcomes and advocating holistic foundations for children’s future success.